Arts Education Management in Higher Education - Emridawati Emridawati (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2016)
Arts education in every educational institution can be said far from part of societies and decision makers’ thinking even it is far from art educators. In general, the potencial of arts education in educationalinstitutions can only seenfrom one side, that is as the developmentof artistic capability. That is whymany policies and ideas that are produced or uttered are not advantageuos for the students’ future needs. Worrying about this phenomenon of the arts education, it is important to discuss it more carefully and more deeply by employing the following management techniques: destination principle, profit principle, achievement principle, integrity principle, unity principle, and friendship principle. Besides, management is also needed to see the change of human resource development such as; planning, organizing, actuating, and controling. Through the above functionsmanagement is expected to be able to give solutionsto face the competitive future. One of the important elements that isrelated to the education strategy is environment setting in that studying in higher education reallygivesencouragement to every student.